148 Posterior Malleolus Fractures: Classification and Patient Outcomes. (28th February 2022) - Banks, P.; Lineham, B.
Abstract: Aim: Posterior malleolus (PM) fractures are a common and significant injury. Historically, only fractures constituting >30% of the joint surface were managed operatively, however more recent research suggests that the type of fracture and injury mechanism carry more importance. This study compared the patient outcome scores with the most common classification systems, percentage tibial plafond involved (PTP) and fixation method. Method: Patients diagnosed with PM fractures between December-2020 and January-2015 were identified and invited to answer a Foot and Ankle Outcome Survey (FAOS). Responding patients had CT scans reviewed by a consultant radiologist. The fractures were classified using Mason Malloy, Haraguchi, Bartonicek and PTP. Groups were further divided into those managed as recommended by each classification. The classifications were correlated against FAOS using Pearson correlation coefficient or one-way ANOVA test as appropriate. Results: 59 patients responded with a completed FAOS. When classifications were measured against FAOS no statistically significant difference was identified (Bartonicek F = 1.78 p = 0.15, Haraguchi = F = 0.41 p = 0.66, Mason Malloy F = 1.24 p = 0.30, PTP = 0.11 p = 0.41). When only those managed as recommended by the classification system were included there remained no significant difference (Bartonicek F = 1.8 p = 0.18, Haraguchi F = 2.4 p = 0.10, Mason Malloy F = 0.25 p = 0.86, PTP = 0.25 p = 0.06). Conclusions: Categorisation of PM fractures by any of the three main classification methods or PTP did not correlate with FAOS in this group including in patients managed as suggested by the classification. Whilst recognising the limitations of this retrospective study this may suggest patient outcome from PM fractures is more significantly influenced by other factors than fracture classification.